Design and Performance Study of SOFC-"GT+ST" System Based on Hydrogen Fuel - Yunrui CHENG; Puyan ZHENG; Haisen YANG; Xia CHENG; Jiagang SONG; Huajian LI (南方能源建设)
[Objective] For the oxygen ion conductive solid fuel cell fueled by hydrogen, the paper proposed a SOFC-"GT+ST" system with the cathode and anode of the fuel cell entering the gas turbine and steam turbine respectively, and analyzed the impact of different parameters on system efficiency, providing reference opinions for hydrogen fuel cell and turbine coupling systems. [Method] A system model was established using the software Ebsilon. The model was compared with the SOFC-GT system under the given parameters. Additionally, the study investigated the effects of fuel utilization, compressor pressure ratio, air flow and SOFC inlet working fluid temperature on the total power generation efficiency of SOFC-"GT+ST" system. [Result] The results show that compared with the SOFC-GT system, the total power generation of the SOFC-"GT+ST" system increases to 73.3 MW, representing a 5.74% improvement over the original system, with a power generation efficiency of 60.13%. The fuel utilization of the fuel cell, the compressor pressure ratio, the cell inlet temperature and the air flow rate all affect the system's total power generation efficiency. Among these factors, there is an optimal value for fuel utilization and a reasonable range for the air flow rate. Additionally, higher cell inlet temperature and compressor pressure ratio lead to higher power generation efficiency of the system. [Conclusion] Under the structure and parameters defined in this study, the optimal value of fuel utilization of fuel cell is 0.85, and the air flow value should be between 35 and 39 kg/s. The improved system can effectively enhance the total power generation efficiency of SOFC and turbine combined power generation system. The results of this study provide a reference for the selection of system parameters.